THE EFFECT OF THE NUMBERED HEAD TOGETHER (NHT) COOPERATIVE LEARNING MODEL ON THE MATHEMATICS LEARNING OUTCOMES OF GRADE IX STUDENTS OF SMP NEGERI 6 BENGKULU CITY - Kusuma, Helti Puji; Susanta, Agus; Sumardi, Hari (Nindikayla Institute, 2024)
This study aims to see whether there is or not the effect of the cooperative numbered head together learning model on the mathematics learning outcomes 9th grade students of SMPN 6 Bengkulu City. The type of research was a quasi-experimental design with The Nonequivalent Pretest-Posttest Control group design. The population in this study were all students of class IX SMPN 6 Bengkulu City. The sample selection used simple random sampling technique, the sample in this study was class IX A which consisted of 25 students as the experimental class and class IX B which consisted of 25 students as the control class. Data collection was carried out using questions pretest and posttest. The results of the hypothesis test showed the sig (2- tailed) value is 0.000 < α = 0.005, with an average student posttest score experiment class of 75,88 and an average student posttest score control class of 58,84. It can be concluded that there is a significant influence of the cooperative Numbered Head Together learning model on the mathematics learning outcomes 9th grade students of SMPN 6 Bengkulu City.